Influenza a virus triggers acute exacerbation of chronic obstructive pulmonary disease by increasing proinflammatory cytokines secretion via NLRP3 inflammasome activation - Shuang Ji; Meng-Yuan Dai; Yun Huang; Xiang-Chun Ren; Meng-Long Jiang; Jin-Ping Qiao; Wen-Ying Zhang; Yuan-Hong Xu; Ji-Long Shen; Ren-Quan Zhang; Guang-He Fei (BMC, 2022)
Abstract Background Influenza A virus (IAV) triggers acute exacerbation of chronic obstructive pulmonary disease (AECOPD), but the molecular mechanisms remain unclear. In this study, we investigated the role of IAV induced NLRP3 inflammasome activation to increase airway inflammation response in the progression of AECOPD. Methods Human bronchial epithelial cells were isolated and cultured from normal and COPD bronchial tissues and co-cultured with IAV. The NLRP3 inflammasome associated genes were identified using RNA sequencing, and the expressions of NLRP3 inflammasome components were measured using qRT-PCR and western blot after cells were transfected with siRNA and treated with MCC950. Moreover, IAV-induced COPD rat models were established to confirm the results; 37 AECOPD patients were included to measure the serum and bronchoalveolar lavage fluid (BALF) of interleukin (IL)-18 and IL-1β. Results Increased levels of NLRP3 inflammasome components were not seen until 6 h post-inoculation in normal cells. However, both cell groups reached peak NLRP3 level at 12 h post-inoculation and maintained it for up to 24 h. ASC, Caspase-1, IL-1β and IL-18 were also elevated in a similar time-dependent pattern in both cell groups. The mRNA and protein expression of the NLRP3 inflammasome components were decreased when COPD cells treated with siRNA and MCC950. In COPD rats, the NLRP3 inflammasome components were elevated by IAV. MCC950 alleviated lung damage, improved survival time, and reduced NLRP3 inflammasome components expression in COPD rats. Additionally, the serum and BALF levels of IL-1β and IL-18 were increased in AECOPD patients. Conclusions NLRP3 inflammasome is activated in COPD patients as a pre-existing condition that is further exacerbated by IAV infection.